Fatty acid amide hydrolase–morphine interaction influences ventilatory response to hypercapnia and postoperative opioid outcomes in children. (January 2017) - Chidambaran, Vidya; Pilipenko, Valentina; Spruance, Kristie; Venkatasubramanian, Raja; Niu, Jing; Fukuda, Tsuyoshi; Mizuno, Tomoyuki; Zhang, Kejian; Kaufman, Kenneth; Vinks, Alexander A; Martin, Lisa J; Sadhasivam, Senthilkumar
Aim: Fatty acid amide hydrolase ( FAAH ) degrades anandamide, an endogenous cannabinoid. We hypothesized that FAAH variants will predict risk of morphine-related adverse outcomes due to opioid–endocannabinoid interactions.Patients & methods: In 101 postsurgical adolescents receiving morphine analgesia, we prospectively studied ventilatory response to 5% CO2 (HCVR), respiratory depression (RD) and vomiting. Blood was collected for genotyping and morphine pharmacokinetics.Results: We found significant FAAH –morphine interaction for missense (rs324420) and several regulatory variants, with HCVR (p < 0.0001) and vomiting (p = 0.0339). HCVR was more depressed in patients who developed RD compared with those who did not (p = 0.0034), thus FAAH –HCVR association predicts risk of impending RD from morphine use.Conclusion: FAAH genotypes predict risk for morphine-related adverse outcomes.